2017
DOI: 10.1136/bmjopen-2017-015833
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of behavioural change techniques in physiotherapy interventions to promote physical activity adherence in patients with hip and knee osteoarthritis: a systematic review protocol

Abstract: IntroductionOsteoarthritis (OA) is a common degenerative articular disease, the highest cause of individual level disability and a significant socioeconomic burden to healthcare services. Patient education and physical activity (PA) prescription are recommended components of interventions in several healthcare guidelines and are commonly provided by physiotherapists. However, these interventions lack long-term clinical effectiveness. Patient adherence to PA prescription requires patients to modify their PA beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…Stroke survivors are health outcome-driven and may not exercise patience until results are yielded. Perhaps, this talks to the missed opportunities by healthcare practitioners in utilising various resources, such as behaviour change models, to enhance stroke survivors’ uptake of physiotherapy interventions (Basset 2015 ; Keogh et al 2015 ; Willet et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke survivors are health outcome-driven and may not exercise patience until results are yielded. Perhaps, this talks to the missed opportunities by healthcare practitioners in utilising various resources, such as behaviour change models, to enhance stroke survivors’ uptake of physiotherapy interventions (Basset 2015 ; Keogh et al 2015 ; Willet et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review was conducted according to a registered (CRD42016039932) and published protocol [35] using methodological guidelines from the Cochrane Collaboration’s Musculoskeletal group [36] and Centre of Reviews and Dissemination (CRD) [37]; and is reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA) [38].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, many studies have found that osteoarthritis patients have immune abnormalities, and abnormal secretions of cytokines might damage cartilage function and metabolism[14,15]. In addition, aggravated gradual decomposition of cartilage matrix can bring irreversible injury to the joint structure of patients, which is manifested as the corresponding clinical symptoms, thus accelerating the progress of articular cartilage injury[16,17]. IL-1ÎČ, IL-6 and TNF-α are secreted from macrophages and immune cells, which mainly come from the lining cells of the synovial membrane.…”
Section: Discussionmentioning
confidence: 99%